79.4k views
1 vote
How would I do this? What would it be?

How would I do this? What would it be?-example-1
User Unplug
by
5.7k points

2 Answers

5 votes

Answer:

Explanation:

You can solve this by substitution method

Since AE is bisector

Angle BAE = angle. EAC

SINCE angle BAE=x+30

EAC= x+30

So, 3x-10= x+30

2x. = 40

x. = 40/2 = 20°

Thank you

User Wes H
by
5.2k points
4 votes

50

Explanation:

Since AE is the bisector of angle BAC,so angle BAE and Angle CAE is equal. Here Angle CAE and Angle EAC is same.

therefore,

m(Angle BAE)=m(Angle EAC)


x + 30 = 3x - 10

or, 2x=40

or, x=20

Hence,

m(Angle EAC)=


3x - 10

=


(3 * 20) - 10 = 60 - 10 = 50

User Dwonisch
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.